(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background & Objectives: Chronic Obstructive Pulmonary Disease (COPD) is the illness with airflow obstruction caused by emphysema, chronic bronchitis, or a combination of both the disorders. It is the third leading cause of death worldwide. Between 20 and 40% of all COPD patients across the globe are never smokers. The primary objective of this study was to evaluate Pulmonary Function Tests (PFTs) in non-smoker COPD patients and compare their results with normal healthy subjects. The study also intended to check the variations in lung function of COPD patients living in urban & rural areas. Materials & Methods: The study was conducted by performing PFTs in 50 non-smoker COPD patients (28 from urban & 22 from rural areas) & comparing them with 50 non-smoker healthy subjects of same age group excluding ex-smokers. Various parameters of PFTs like FVC, FEV1, FEV1/FVC, PEFR & MVV were assessed & compared. For statistical data analysis unpaired t-Test was applied. Results: The mean values of PFT parameters such as FVC, FEV1, FEV1/FVC, PEFR & MVV are very significantly differed between COPD patients & healthy subjects (p<0.01). Although the data is not statistically significant between total COPD patients, urban & rural COPD patients, mean values of above PFT parameters are higher in total COPD patients than urban while higher in rural compared to total COPD patients (p>0.05). The mean values of above PFT parameters are not significant statistically between urban & rural COPD patients (p>0.05). Conclusion: The study indicates that as compared to normal subjects, in patients of COPD there is great reduction in mean values for FVC, FEV1, PEFR, FEV1/FVC%, & MVV irrespective of their residing location which is suggestive of an increase air way obstruction with reduced values of various PFT parameters. The study also shows that there is no significant difference in mean values of various parameters between urban & rural areas.